Piezoelectric laminate, piezoelectric element, and method for manufacturing piezoelectric laminate

By setting a base layer of zirconium nitride between the piezoelectric film and the electrode layer, the problem of the influence of crystal structure matching is solved, the crystal orientation of the piezoelectric film is improved, and excellent piezoelectric properties are achieved.

CN119213902APending Publication Date: 2024-12-27AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380040506.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-16
Filing Date
2023-04-28
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the crystal structure or lattice matching between the piezoelectric film and the electrode layer has a great influence, limiting the crystal orientation of the piezoelectric film.

Method used

A base layer containing zirconium nitride is provided between the piezoelectric film and the electrode layer, and the contact between the zirconium nitride base layer and the piezoelectric film is formed by sputtering method, thereby improving the c-axis orientation of the piezoelectric film.

Benefits of technology

Effectively eliminate the influence of crystal structure or lattice matching, improve the crystal orientation of the piezoelectric film, significantly improve the c-axis orientation, and especially show excellent piezoelectric properties in the case of aluminum nitride films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213902A_ABST
    Figure CN119213902A_ABST
Patent Text Reader

Abstract

The present invention relates to a piezoelectric laminate having a substrate and a laminated film provided on at least one surface of the substrate, the laminated film including an electrode layer, a base layer, and a piezoelectric thin film in this order from the substrate side, the base layer being in contact with the piezoelectric thin film, the base layer containing zirconium nitride, and the piezoelectric thin film containing zirconium nitride. The piezoelectric thin film has a hexagonal wurtzite structure oriented in the c-axis direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a piezoelectric stack, a piezoelectric element, and a method for manufacturing the piezoelectric stack. Background Art

[0002] In recent years, micro-electromechanical systems (MEMS) have attracted much attention. MEMS is a device that integrates mechanical components and electronic circuits on a single substrate using microfabrication technology. Piezoelectric laminates are used in MEMS that have functions such as sensors, filters, collectors, or actuators.

[0003] It is known that a piezoelectric laminate is formed by arranging a material having a hexagonal wurtzite structure, namely aluminum nitride (AlN), on a substrate such as silicon (Si) or sapphire or a glass substrate. The aluminum nitride has piezoelectricity and pyroelectricity in the c-axis direction. Therefore, an aluminum nitride film, namely a c-axis oriented aluminum nitride film, is used as a component of a piezoelectric thin film resonator, MEMS, etc. by utilizing its piezoelectricity. In addition, an aluminum nitride film is used as a sensor, etc. by utilizing its pyroelectricity.

[0004] Thus, many studies have been conducted to obtain aluminum nitride thin films with high c-axis orientation. For example, Patent Documents 1 and 2 disclose that the c-axis orientation can be improved by providing a base layer of tungsten or platinum between a silicon substrate or a glass substrate and aluminum nitride. Patent Document 3 discloses that good crystallinity can be obtained by using a material having the same hexagonal wurtzite structure as the base layer of aluminum nitride.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2004-6535

[0008] Patent Document 2: Japanese Patent Application Publication No. 2004-265899

[0009] Patent Document 3: Japanese Patent Application Publication No. 2019-145677 Summary of the invention

[0010] However, in the existing methods, in order to improve the crystal orientation, the electrode layer in contact with the piezoelectric film needs to have the same crystal structure or lattice matching, which limits the selection of electrode materials constituting the electrode layer.

[0011] Therefore, an object of the present invention is to provide a method for eliminating the influence of the crystal structure or lattice matching of the piezoelectric film and the electrode layer and improving the crystal orientation of the piezoelectric film.

[0012] The present inventors have found that the above-mentioned problems can be solved by providing an underlayer containing zirconium nitride between the piezoelectric thin film and the electrode layer, thereby completing the present invention.

[0013] That is, one embodiment of the present invention relates to the following contents.

[0014] [1] A piezoelectric laminate comprising a substrate and a laminate film disposed on at least one surface of the substrate, wherein the laminate film comprises an electrode layer, a base layer and a piezoelectric film in order from the substrate side, the base layer being in contact with the piezoelectric film, the base layer containing zirconium nitride, and the piezoelectric film having a hexagonal wurtzite structure oriented in the c-axis direction.

[0015] [2] The piezoelectric stack according to [1] above, wherein the piezoelectric thin film contains aluminum nitride, and the aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

[0016] [3] The piezoelectric laminate according to [1], wherein the zirconium nitride has a chemical formula of ZrN X It means that the degree of nitridation represented by x in the above chemical formula is in the range of 0<x<2.

[0017] [4] The piezoelectric stack according to [3] above, wherein the degree of nitridation is in the range of 1<x<2.

[0018] [5] The piezoelectric stack according to [1] above, wherein the thickness of the base film is 0.2 nm to 40 nm.

[0019] [6] The piezoelectric stack according to [5] above, wherein the thickness of the base film is 0.4 nm to 20 nm.

[0020] [7] The piezoelectric stack according to [1] above, wherein the arithmetic mean roughness (Ra) of the piezoelectric film is 4.0 nm or less.

[0021] [8] The piezoelectric laminate according to [1] above, wherein the peak intensity ratio of the (101) plane / (002) plane in the X-ray diffraction pattern obtained by measuring the piezoelectric film by an out-of-plane method {(101) plane / (002) plane} is less than 0.25.

[0022] [9] The piezoelectric laminate according to [1] above, wherein the peak intensity ratio of the (101) plane / (002) plane in the X-ray diffraction pattern obtained by measuring the piezoelectric film by an out-of-plane method {(101) plane / (002) plane} is less than 0.1.

[0023]

[10] The piezoelectric stack according to [1] above, wherein the piezoelectric thin film has a thickness of 100 nm to 10 μm.

[0024]

[11] A piezoelectric element comprising the piezoelectric laminate according to any one of [1] to

[10] above.

[0025]

[12] A method for manufacturing a piezoelectric stack, which is a method for manufacturing a piezoelectric stack having a substrate and a stacked film arranged on at least one surface of the substrate, comprising the following steps: preparing a substrate, and sequentially forming an electrode layer, a base layer and a piezoelectric film on at least one surface of the substrate; the base layer contains zirconium nitride, the piezoelectric film has a hexagonal wurtzite structure oriented in the c-axis direction, and the piezoelectric film is formed so as to be in contact with the base layer.

[0026]

[13] The method for producing a piezoelectric stack according to

[12] above, wherein the piezoelectric film contains aluminum nitride, and the aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

[0027]

[14] The method for producing a piezoelectric stack according to

[12] or

[13] above, wherein the film formation is performed by a sputtering method.

[0028] In addition, another embodiment of the present invention relates to the following contents.

[0029] [1] A piezoelectric laminate having a substrate and a laminate film arranged on at least one surface of the substrate, wherein the laminate film includes an electrode layer, a base layer and a piezoelectric film in order from the substrate side, the base layer is in contact with the piezoelectric film, the base layer contains zirconium nitride, and the piezoelectric film has a hexagonal wurtzite structure oriented in the c-axis direction.

[0030] [2] The piezoelectric laminate according to [1], wherein the piezoelectric thin film contains aluminum nitride, and the aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

[0031] [3] The piezoelectric laminate according to [1] or [2], wherein the zirconium nitride has a chemical formula of ZrN X It means that the degree of nitridation represented by x in the above chemical formula is in the range of 0<x<2.

[0032] [4] The piezoelectric stack according to [3], wherein the degree of nitridation is in the range of 1<x<2.

[0033] [5] The piezoelectric stack according to any one of [1]' to [4]' above, wherein the thickness of the base film is 0.2 nm to 40 nm.

[0034] [6] The piezoelectric stack according to [5], wherein the thickness of the base film is 0.4 nm to 20 nm.

[0035] [7] The piezoelectric stack according to any one of [1]' to [6]', wherein the piezoelectric thin film has an arithmetic mean roughness (Ra) of 4.0 nm or less.

[0036] [8] The piezoelectric laminate according to any one of [1]' to [7]', wherein the peak intensity ratio of the (101) plane / (002) plane in the X-ray diffraction pattern of the piezoelectric film measured by an out-of-plane method {(101) plane / (002) plane} is 0.25 or less.

[0037] [9] The piezoelectric laminate according to any one of [1]' to [8]', wherein the peak intensity ratio of (101) plane / (002) plane in an X-ray diffraction pattern of the piezoelectric film measured by an out-of-plane method {(101) plane / (002) plane} is less than 0.1.

[0038]

[10] The piezoelectric stack according to any one of [1]' to [9]', wherein the piezoelectric thin film has a thickness of 100 nm to 10 μm.

[0039]

[11] A piezoelectric element comprising the piezoelectric laminate according to any one of [1]' to

[10] '.

[0040]

[12] A method for manufacturing a piezoelectric stack, which is a method for manufacturing a piezoelectric stack having a substrate and a stacked film arranged on at least one surface of the substrate, comprising the following steps: preparing a substrate, and sequentially forming an electrode layer, a base layer and a piezoelectric film on at least one surface of the substrate; the base layer contains zirconium nitride, the piezoelectric film has a hexagonal wurtzite structure oriented in the c-axis direction, and the piezoelectric film is formed so as to be in contact with the base layer.

[0041]

[13] The method for producing a piezoelectric stack according to

[12] , wherein the piezoelectric thin film contains aluminum nitride, and the aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

[0042]

[14] The method for producing a piezoelectric stack according to

[12] ' or

[13] ', wherein the film formation is performed by a sputtering method.

[0043] According to the present invention, the influence of the crystal structure or lattice matching of the piezoelectric film and the electrode layer can be eliminated, and the crystal orientation of the piezoelectric film can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic cross-sectional view of the piezoelectric stack according to the present embodiment. DETAILED DESCRIPTION

[0045] Hereinafter, the contents of the embodiments of the present invention will be described with reference to the drawings, etc. However, the present invention includes many different modes and should not be interpreted as being limited to the contents of the embodiments illustrated below.

[0046] <Piezoelectric laminate>

[0047] Reference Figure 1 The structure and manufacturing method of the piezoelectric stack 100 according to this embodiment will be described.

[0048] [Structure of Piezoelectric Laminated Body]

[0049] Figure 1 2 is a cross-sectional schematic diagram illustrating the structure of the piezoelectric stack 100 according to the present embodiment. Figure 1 As shown, the piezoelectric laminate 100 includes a substrate 101 and a laminate film 105 provided on at least one surface of the substrate 101. The laminate film 105 includes an electrode layer 102, a base layer 103, and a piezoelectric film 104 in this order from the substrate side. Here, the base layer 103 is in contact with the piezoelectric film 104.

[0050] (Substrate)

[0051] The substrate 101 may be any substrate as long as the laminated film 105 can be formed on the surface thereof. The thickness, material, etc. are not particularly limited, and any conventionally known substrate can be used.

[0052] As the substrate 101, for example, a silicon (Si) single crystal, or a substrate having a silicon, diamond or other polycrystalline film formed on the surface of a substrate such as a Si single crystal, can be used. The substrate 101 can also be a stainless steel (SUS, etc.) metal substrate, an amorphous substrate such as glass, a film such as polyethylene terephthalate (PET), etc.

[0053] (Electrode layer)

[0054] The electrode layer 102 is not particularly limited, and an electrode layer generally used in the piezoelectric stack 100 can be used.

[0055] The electrode material constituting the electrode layer 102 may be, for example, a metal material such as aluminum (Al), a transition metal such as molybdenum (Mo), titanium (Ti), chromium (Cr), tantalum (Ta), iridium (Ir), and nickel (Ni), a noble metal such as ruthenium (Ru), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), and copper (Cu), a conductive metal oxide such as ruthenium oxide (RuO2), or a conductive metal nitride such as chromium nitride (CrN). In addition, the above materials may be combined to form the electrode layer 102.

[0056] The thickness of the electrode layer 102 is not particularly limited, and is preferably 5 to 1000 nm, for example. From the perspective of forming a continuous film, the thickness is preferably 5 nm or more. From the perspective of preventing the continuous film from being lost due to cracks, the thickness is preferably 1000 nm or less.

[0057] The arithmetic mean roughness (Ra) of the electrode layer 102 is not particularly limited, and is preferably 0.1 to 10 nm, for example. Here, from the viewpoint of obtaining good electrical conductivity due to the presence of crystal grains, the arithmetic mean roughness (Ra) is preferably 0.1 nm or more. In addition, from the viewpoint of preventing the decrease in electrical conductivity caused by grain boundary scattering, the arithmetic mean roughness (Ra) is preferably 10 nm or less.

[0058] The specific resistance of the electrode layer 102 is preferably 1×10 -6 ~1×10 -2 Ω·cm. Here, from the viewpoint of ensuring good conductivity, the above-mentioned specific resistance is preferably 1×10 -2 Ω·cm or less, particularly preferably 1×10 -3 Ω·cm or less. The lower limit of the resistivity is not particularly limited, but is usually 1×10 -6 Ω·cm or more.

[0059] (basal layer)

[0060] The base layer 103 is a layer formed on the electrode layer 102 directly or via other layers, and improves the crystal orientation of the piezoelectric thin film 104 provided on the base layer 103. The base layer 103 is in direct contact with the piezoelectric thin film 104.

[0061] It is known that the crystal orientation of the piezoelectric thin film 104 is greatly affected by the surface of the layer on which the piezoelectric thin film 104 is provided.

[0062] In this regard, the present inventors have found that when a base layer 103 containing zirconium nitride is provided and a piezoelectric film 104 is provided directly thereon, when the piezoelectric film 104 has a wurtzite structure with hexagonal crystals oriented in the c-axis direction, its crystal orientation is improved. In particular, when the piezoelectric film 104 is a film containing aluminum nitride having a wurtzite structure with hexagonal crystals oriented in the c-axis direction, the c-axis orientation of the piezoelectric film 104 can be particularly improved.

[0063] The base layer 103 contains zirconium nitride. Zirconium nitride has a chemical formula of ZrN XIn the chemical formula, x represents the degree of nitridation. The degree of nitridation x is greater than 0, preferably greater than 0 and less than 2. Here, the degree of nitridation x is preferably greater than 1, more preferably greater than 1.1, and preferably less than 2, more preferably less than 1.65. By falling within the above range, the c-axis orientation of the piezoelectric film 104 is further improved. In addition, this effect is significant when the piezoelectric film 104 contains aluminum nitride.

[0064] It should be noted that the identification of the nitridation degree x can be determined by the Rutherford backscattering analysis (RBS) method. In addition, when there are multiple samples, the nitridation degree x can be measured for two or more samples by the above-mentioned RBS method and ellipsometry, and their correlation coefficients can be derived. Then, for other samples, the nitridation degree x can be calculated by the RBS method based on the measurement results of the ellipsometry.

[0065] The thickness of the base layer 103 is not particularly limited, but is preferably 0.1 to 100 nm. From the perspective of further improving the c-axis orientation of the piezoelectric film 104, the thickness is preferably 0.1 nm or more, more preferably 0.2 nm or more, and further preferably 0.4 nm or more. In addition, it is preferably 100 nm or less, more preferably 40 nm or less, and particularly preferably 20 nm or less.

[0066] (Piezoelectric film)

[0067] The piezoelectric film 104 has a hexagonal wurtzite structure oriented in the c-axis direction. The presence of the hexagonal wurtzite structure can be confirmed by, for example, X-ray diffraction (XRD), X-ray absorption spectroscopy (XAFS, EXAFS), and the like.

[0068] The piezoelectric properties of the piezoelectric film 104 having a hexagonal wurtzite structure are oriented in the

[002] direction of the hexagonal wurtzite structure. That is, the piezoelectric film 104 can achieve excellent piezoelectric properties by orienting the (002) plane of the hexagonal wurtzite structure (c-axis orientation).

[0069] In this specification, "oriented in the c-axis direction" or "c-axis orientation" means that the peak intensity ratio of (101) plane / (002) plane in the X-ray diffraction pattern measured by the out-of-plane method of the piezoelectric film is less than 0.3.

[0070] The piezoelectric film 104 is a layer having at least one of piezoelectricity and pyroelectricity, and is a crystalline film having a hexagonal wurtzite structure oriented in the c-axis direction.

[0071] As the piezoelectric film 104, for example, a thin film of aluminum nitride (AlN), ZnO, GaN, etc. is preferably used. Among them, from the viewpoint of manufacturing adaptability and the viewpoint of improving the crystallinity in the base layer described later, it is particularly preferred to contain AlN, and more preferably AlN has a hexagonal wurtzite structure oriented in the c-axis direction.

[0072] The piezoelectric film 104 is preferably 0.1 to 5.5 nm. Here, the piezoelectric film 104 is preferably smooth and has a small arithmetic mean roughness (Ra). The arithmetic mean roughness (Ra) of the surface of the piezoelectric film 104 is preferably 5.5 nm or less, more preferably 5.0 nm or less, further preferably 4.0 nm or less, and particularly preferably 3.5 nm or less. In addition, the lower limit of the arithmetic mean roughness (Ra) is not particularly limited. From the perspective of adhesion when forming a laminated film, it is preferably 0.1 nm or more, more preferably 0.2 nm or more, and most preferably 0.3 nm or more.

[0073] The arithmetic mean roughness (Ra) of the surface of the piezoelectric thin film refers to the arithmetic mean roughness of the surface on the side in contact with the base layer 103. The arithmetic mean roughness (Ra) is measured using an atomic force microscope (AFM).

[0074] The film thickness of the piezoelectric film 104 is not particularly limited, but is preferably 100 nm to 10 μm. Here, from the perspective of ensuring good crystal orientation and fully ensuring piezoelectric properties, the film thickness is preferably 100 nm or more, more preferably 250 nm or more, further preferably 500 nm or more, and most preferably 1 μm or more. On the other hand, from the perspective of growing crystals without generating cracks, the film thickness is preferably 10 μm or less, further preferably 7.5 μm or less, and most preferably 5 μm or less.

[0075] In the X-ray diffraction pattern obtained by measuring the piezoelectric film 104 by the out-of-plane method, the peak intensity ratio of the (101) plane to the (002) plane {(101) plane / (002) plane} is preferably 0 to 0.25. Here, from the perspective of further ensuring the hexagonal wurtzite structure oriented in the c-axis direction and fully ensuring the piezoelectric properties, the peak intensity ratio is preferably 0.25 or less, more preferably 0.1 or less, further preferably 0.05 or less, and most preferably 0.01 or less. In addition, the lower limit of the peak intensity ratio is not particularly limited and can be 0.

[0076] It should be noted that the piezoelectric laminate of the present embodiment may include layers other than the above-mentioned substrate, electrode layer, base layer, and piezoelectric thin film within a range not impairing the effects of the present invention.

[0077] For example, a bonding layer for bonding the substrate to the metal may be provided between the substrate and the electrode layer, and a bonding layer for bonding the electrode to the base layer may be provided between the electrode layer and the base layer. In addition, a thermal oxidation film may be provided on at least one surface of the substrate. Furthermore, an upper electrode layer and a protective layer may be provided on the surface on the side opposite to the electrode layer side. The above layers may all be conventionally known layers.

[0078] The piezoelectric laminate of this embodiment can be applied to piezoelectric elements. The piezoelectric element can be applied to piezoelectric elements using the piezoelectric effect, such as gyro sensors, impact sensors, and microphones, as well as piezoelectric elements using the inverse piezoelectric effect, such as actuators, inkjet heads, speakers, buzzers, and resonators.

[0079] [Method for producing a piezoelectric laminate]

[0080] The method for manufacturing a piezoelectric stack according to the present embodiment includes the steps of preparing a substrate, and sequentially forming an electrode layer, a base layer, and a piezoelectric thin film on at least one surface of the substrate.

[0081] The base layer contains zirconium nitride, and the piezoelectric thin film has a hexagonal wurtzite structure oriented in the c-axis direction. The piezoelectric thin film is formed so as to be in contact with the base layer.

[0082] The substrate, electrode layer, base layer and piezoelectric film may be the substrate, electrode layer, base layer and piezoelectric film described in the above [Structure of piezoelectric stack], respectively. In addition, the obtained piezoelectric stack is preferably the piezoelectric stack described in the above [Structure of piezoelectric stack].

[0083] That is, in the piezoelectric laminate obtained by the production method of this embodiment, the base layer is in contact with the piezoelectric thin film, the base layer contains zirconium nitride, and the piezoelectric thin film has a hexagonal wurtzite structure oriented in the c-axis direction.

[0084] (Substrate Preparation)

[0085] As the substrate, for example, the above-mentioned substrates may be used, and a commercially available substrate may be used or a fabricated substrate may be used.

[0086] (Film formation of laminated film)

[0087] A stacked film 105 is formed on at least one surface of the substrate prepared above. The stacked film 105 is formed in the order of an electrode layer, a base layer, and a piezoelectric film, all of which can adopt, for example, a physical vapor deposition method, a chemical vapor deposition method (CVD method), etc. As a physical vapor deposition method, for example, a physical vapor deposition method, a PVD method, a sputtering method, etc. can be cited. Among them, from the viewpoint of being able to control the doping amount in a wide range, a sputtering method is particularly preferred, and a magnetron sputtering method and a digital sputtering method are particularly preferred.

[0088] The electrode layer may be provided directly on at least one surface of the substrate, or may be provided via an adhesion layer, etc. The electrode layer may be a single layer, or may be composed of two or more layers.

[0089] The base layer may be provided directly on the electrode layer or via an adhesion layer or the like.

[0090] The base layer contains zirconium nitride. When the base layer is formed by sputtering, the zirconium nitride ZrN can be adjusted by controlling the film forming conditions. X The composition of the film is the value of the nitridation degree x. Examples of film forming conditions include the temperature of the substrate 100 during film formation, the film forming pressure, the composition of the introduced gas, the target composition, and the post-heat treatment temperature.

[0091] Zirconium nitride ZrN X The target may contain impurities such as carbon and oxygen which are inevitably introduced during film formation at a maximum of about 10 at% (atoms%). When the sputtering method is used, the maximum allowable impurity content in the target is about 10 at%. That is, the zirconium nitride ZrN X The impurities contained in the target Zr and the target of the material constituting the piezoelectric film, for example, the impurities contained in the target Al when it is aluminum nitride AlN, include Hf, Ti, Sc, V, Nb, Ta, Cr, Mo, W, O, C and the like.

[0092] When forming the base layer, the piezoelectric film may contain doping elements within a range capable of maintaining the hexagonal wurtzite structure. For example, when the piezoelectric film contains aluminum nitride, by including Sc, Y, Mg, Ca, Sr, Zr, Hf, V, Nb and other elements as doping elements, strain is applied to the aluminum nitride to improve the piezoelectric performance. In particular, the Sc element is preferred in improving the piezoelectric performance, and in this case, it can be doped to about 43at%.

[0093] Zirconium nitride ZrN in the substrate X The nitridation degree x can be adjusted by the nitrogen flow rate during film formation. For example, when the nitridation degree x is adjusted to a range of 0<x<2, the nitrogen flow rate is preferably 20% or more, and particularly preferably 40% or more, in terms of the ratio {N2 / (Ar+N2)}. Furthermore, even when the above ratio is 100%, the film forming pressure can be increased by increasing the nitrogen flow rate, thereby adjusting to a larger amount of nitrogen, and the nitridation degree x can be made close to 2.

[0094] The film forming pressure is preferably 0.05 to 10 Pa. From the viewpoint of crystal density and orientation, the film forming pressure is preferably 0.05 Pa or more, more preferably 0.1 Pa or more, and is preferably 10 Pa or less, more preferably 1 Pa or less.

[0095] The substrate temperature during the formation of the base layer is preferably room temperature to 600° C. or lower, and more preferably 250° C. or lower.

[0096] In order to fully exert the effect of the base layer, it is preferred to continuously form the film without breaking the vacuum state not only when the base layer is formed, but also until the electrode layer, the base layer and the piezoelectric film are all formed. In particular, if the vacuum state is broken when the base layer and the piezoelectric film are formed, oxygen as an impurity will mix into the base layer, and sometimes the characteristics of the base layer cannot be exerted. In this case, good interface characteristics cannot be obtained, so it is preferred to continuously form the film in a vacuum state.

[0097] The piezoelectric film is formed directly on the substrate layer.

[0098] As long as the piezoelectric thin film is a thin film having a hexagonal wurtzite structure oriented in the c-axis direction, a conventionally known substance can be used and formed by a conventionally known method.

[0099] For example, when making a thin film of aluminum nitride having a hexagonal wurtzite structure oriented in the c-axis direction, the film formation conditions when forming the film by sputtering are, for example, pressure: 0.05~10Pa, nitrogen partial pressure ratio: 20~100%, substrate temperature: 25~200°C, etc.

[0100] Example

[0101] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0102] Examples 1 to 21 are embodiments, and Examples 22 to 28 are comparative examples.

[0103] (Example 1)

[0104] As a substrate, a soda-lime glass having a size of 100 mm×100 mm×2 mm was used. An electrode layer was provided on one surface of the substrate according to the following procedure. The electrode layer was formed of only one Ti layer of the lower electrode layer.

[0105] The lower electrode layer is formed by placing the substrate in the vacuum chamber of the sputtering device and then evacuating the vacuum chamber to reduce the pressure to 10 -3 It is carried out after Pa is below.

[0106] Film forming equipment: Vertical inline magnetron sputtering (manufactured by ULVAC)

[0107] Sputtering target: Ti metal (high-purity chemical, purity 3N)

[0108] Introduced gas: Argon (purity = 99.9% or more) 80 sccm

[0109] Film forming pressure: 0.4Pa

[0110] Film thickness: 150nm

[0111] Substrate heating temperature: room temperature

[0112] Next, zirconium nitride (ZrN) was formed on the electrode layer by sputtering under the following conditions: X ) as the base layer.

[0113] The base layer is formed by placing the sample on which the electrode layer is formed in the vacuum chamber of the sputtering device without breaking the vacuum after the electrode layer is formed, and then the vacuum chamber is evacuated to reduce the pressure to 10 -3 Pa or less under the following conditions.

[0114] The base layer is formed by the same apparatus as that used to form the lower electrode layer.

[0115] Sputtering target: Zr metal (produced by Tanaka Kikinzoku, purity 2N2 (value including Hf))

[0116] Introduced gas: Nitrogen (purity = 99.9% or more) 80 sccm

[0117] Film forming pressure: 0.4Pa

[0118] Film thickness: 10nm

[0119] Substrate heating temperature: room temperature

[0120] Next, aluminum nitride (AlN) is formed as a piezoelectric thin film on the base layer according to the following steps.

[0121] The piezoelectric film is formed by reducing the pressure to 10 without breaking the vacuum. -3 It is carried out after Pa is below.

[0122] The piezoelectric thin film is formed by the same apparatus as that used to form the lower electrode layer and the base layer.

[0123] Sputtering target: Made by Kojun Chemical Co., Ltd., Al metal (3N)

[0124] Introduced gas: a mixture of nitrogen (purity = 99.9% or more) 40 sccm and argon (purity = 99.9% or more) 40 sccm

[0125] N2 / (Ar+N2) mixing ratio: 0.5

[0126] Film forming pressure: 0.4Pa

[0127] Substrate heating temperature: room temperature

[0128] Film thickness: 1μm

[0129] In this way, a lower electrode, a ZrN substrate as a base layer, and a X A piezoelectric film and a piezoelectric laminate of aluminum nitride (AlN) as a piezoelectric thin film.

[0130] (Examples 2~6)

[0131] In Examples 2 to 6, except that the gas introduced into the base layer and the mixing ratio were changed to the conditions shown in Table 1, the film was formed by the same procedure as in Example 1 to produce a piezoelectric laminate.

[0132] (Examples 7~10)

[0133] In Examples 7 to 10, a Si substrate having a thermal oxide film with a thickness of 1 μm formed on both surfaces was used as the substrate. The size of the substrate was 100 mm×100 mm×0.675 mm. In addition, the introduction gas and the mixing ratio of the base layer were changed to the conditions shown in Table 1. Except for this, the film was formed by the same steps as in Example 1 to produce a piezoelectric laminate.

[0134] (Examples 11~17)

[0135] In Examples 11 to 17, except that the film thickness of the base layer was changed to the conditions shown in Tables 1 and 2, the film was formed by the same procedure as in Example 1 to produce a piezoelectric laminate.

[0136] (Examples 18~21)

[0137] In Examples 18 to 21, except that the film thickness of the piezoelectric thin film was changed to the conditions shown in Table 2, the film was formed by the same procedure as in Example 1 to produce a piezoelectric laminate.

[0138] (Example 22)

[0139] In Example 22, except that the gas introduced into the base layer was changed to argon only, the film was formed by the same steps as in Example 1 to produce a piezoelectric laminate.

[0140] (Example 23)

[0141] In Example 23, a Si substrate with thermal oxide films formed on both sides was used as the substrate. The size of the substrate was 100 mm×100 mm×0.675 mm. Furthermore, the piezoelectric laminate was formed by the same steps as in Example 1 except that the gas introduced into the base layer was changed to only argon.

[0142] (Examples 24~26)

[0143] In Examples 24 to 26, except that the base layer was not formed and the film thickness of the piezoelectric thin film was changed to the conditions shown in Table 2, the films were formed by the same procedure as in Example 1 to produce piezoelectric laminates.

[0144] (Example 27)

[0145] In Example 6, the niobium nitride film (NbN X ) as the base layer. In the film formation of the base layer, the piezoelectric laminate was produced by the same steps as in Example 1 except that the target material was Nb metal and the power used was changed to 500 W.

[0146] (Example 28)

[0147] In Example 28, the titanium nitride (TiN X ) as the base layer. In the film formation of the base layer, the piezoelectric laminate was produced by the same steps as in Example 1 except that the target material was Ti metal and the power used was changed to 500 W.

[0148] <Evaluation>

[0149] The following measurements and evaluations were performed on each of the obtained piezoelectric laminates.

[0150] (Crystallinity of piezoelectric film)

[0151] XRD measurement was performed using an X-ray diffractometer (MiniFlexII manufactured by Rigaku Corporation). The sample was set so as to evaluate diffraction in the direction perpendicular to the substrate, and 2θ / θ scanning was performed with a divergence slit of 1.25°, a scattering slit of 1.25°, a receiving slit of 0.3 mm, and a 2θ range of 30° to 60°.

[0152] After background correction, the peak intensity ratio {(101) plane / (002) plane} was calculated from the ratio of the diffraction intensity of the (002) plane appearing at 2θ=35°~37° of the AlN crystal to the diffraction intensity of the (101) plane appearing at 2θ=37°~39° to evaluate the orientation.

[0153] The peak intensity ratio of (101) plane / (002) plane was evaluated using 5 criteria. If the criteria were 2 or more, it was determined that orientation was possible. The results are shown in Tables 1 and 2, "Piezoelectric thin film (aluminum nitride) c-axis orientation (criteria)".

[0154] Standard 1: greater than 0.25 and less than 1.0

[0155] Standard 2: greater than 0.10 and less than 0.25

[0156] Standard 3: greater than 0.05 and less than 0.10

[0157] Standard 4: greater than 0.01 and less than 0.05

[0158] Standard 5: 0.01 or less

[0159] (Arithmetic mean roughness of the piezoelectric film surface)

[0160] The arithmetic mean roughness (Ra) of the piezoelectric film was measured using an atomic force microscope (AFM).

[0161] The definition of arithmetic mean roughness (Ra) complies with JIS B 0601-2001.

[0162] If the arithmetic mean roughness (Ra) is 5.5 nm or less, it can be judged to have good flatness, and if it is 4 nm or less, it can be judged to have better flatness. The results are shown in Tables 1 and 2, "Arithmetic mean roughness Ra (nm) of piezoelectric film (aluminum nitride)".

[0163] Device: Made by SII Nanotechnology, Model: S-Image

[0164] (Nitriding degree x)

[0165] The "nitridation degree x" of the base layer is calculated from the "refractive index n" by the following method. The following is an explanation.

[0166] First, in order to form a reference, a base layer 1 and a base layer 2 were formed to a thickness of 20 nm under the following “film forming condition 1” and “film forming condition 2”, respectively.

[0167] Base layer 1: Film forming conditions 1 Power used: 700 W, Ar: 40 sccm, N2: 10 sccm, Film forming pressure: 0.37 Pa

[0168] Base layer 2: Film forming conditions 2: Power 700 W, Ar: 0 sccm, N2: 40 sccm, Film forming pressure: 0.35 Pa

[0169] For quantitative analysis of the base layer 1 and the base layer 2, the element ratio of Zr to N in the zirconium nitride constituting the crystallinity enhancing layer, i.e., ZrN X The value of the nitriding degree x in .

[0170] (Refractive index n)

[0171] Polarization information was measured at wavelengths of 250 nm to 2500 nm using a spectroscopic ellipsometer (manufactured by JA Woollam, M-2000). The obtained polarization information was used to fit an optical model and the value of the refractive index n at a wavelength of 500 nm was determined.

[0172] The results of the nitridation degree x and the refractive index n of the base layer 1 and the base layer 2 are as follows.

[0173] Evaluation results of the base layer 1: Nitriding degree x = 1.02 (evaluated by RBS), refractive index n (wavelength: 500 nm) = 1.25

[0174] Evaluation results of the base layer 2: Nitriding degree x = 1.60 (evaluated by RBS), refractive index n (wavelength: 500 nm) = 3.82

[0175] The following correlation equation was obtained from the evaluation results of the base layer 1 and the base layer 2.

[0176] Nitriding degree x (1≤x≤2) = 0.2333 × refractive index n (wavelength: 500nm) + 0.7073

[0177] The piezoelectric laminates of Examples 1 to 28 were measured for refractive index n at a wavelength of 500 nm by the above method, and the nitridation degree x was calculated from the above correlation formula. The results are shown in Tables 1 and 2 under "underlayer nitridation degree x".

[0178] [Table 1]

[0179]

[0180] [Table 2]

[0181]

[0182] (ZrN X Nitrogen flow dependence)

[0183] Examples 1 to 6 in Table 1 and Table 2 are obtained by controlling the ZrN by changing the gas flow rate during the film formation of the base layer when the substrate is made of soda lime glass. X The results are shown when the degree of nitridation is x. In addition, Examples 7 to 10 are the same results when the substrate is a Si substrate. The results of the orientation in the c-axis direction estimated from the peak intensity ratio measured by XRD of the piezoelectric film composed of AlN with a film thickness of 1 μm and the arithmetic mean roughness (Ra) measured by AFM are also shown.

[0184] According to these results, when the nitriding degree x is 1.13 to 1.63, the arithmetic mean roughness (Ra) is less than 4 nm, and the peak intensity ratio of {(101) plane / (002) plane} is less than 0.25, that is, above standard 2, resulting in a piezoelectric laminate with good surface shape and excellent orientation.

[0185] On the other hand, when the base layer is Zr as in Examples 22 and 23, when the base layer is not inserted as in Examples 24 to 26, or when the base layer is a metal nitride such as NbN or TiN as in Examples 27 and 28, the peak intensity ratio of {(101) plane / (002) plane} is greater than 0.25, that is, standard 1, and a piezoelectric laminate with c-axis orientation cannot be obtained. In addition, the film has a relatively coarse arithmetic mean roughness. It should be noted that "OR" (Over Range) in the arithmetic mean roughness of Examples 26 and 27 in Table 2 indicates that it cannot be properly evaluated.

[0186] Examples 11 to 17 in Table 1 and Table 2 show that the ZrN X When the film thickness varies between 0.2 nm and 50 nm, the orientation in the c-axis direction of a piezoelectric thin film composed of AlN with a film thickness of 1 μm was estimated from the peak intensity ratio obtained by XRD measurement, and the arithmetic mean roughness (Ra) was measured by AFM.

[0187] It can be seen that ZrN X When the film thickness is 0.2nm to 40nm, the arithmetic mean roughness (Ra) is 4nm or less, and the peak intensity ratio of {(101) plane / (002) plane} is 0.25 or less. X When the film thickness is 0.4 nm to 20 nm, the peak intensity ratio of {(101) plane / (002) plane} is 0.01 or less, and a piezoelectric laminate having a good surface shape and excellent orientation is obtained.

[0188] In addition, Examples 18 to 21 in Table 2 show that the ZrN X When the film nitridation degree x=1.6 and the film thickness is 10nm, and the film thickness of AlN is changed, the orientation in the c-axis direction is estimated from the peak intensity ratio obtained by XRD measurement and the arithmetic mean roughness (Ra) measured by AFM. X When the film thickness is in the range of 100 nm to 3 μm, the arithmetic mean roughness (Ra) is less than 4 nm, and the peak intensity ratio of {(101) plane / (002) plane} is less than 0.25, and a piezoelectric laminate having a good surface shape and excellent orientation is obtained. On the other hand, it was confirmed that in Examples 24 to 26 without a base film, sufficient orientation was not obtained, and cracks were generated in the thick region of the piezoelectric film composed of AlN.

[0189] Finally, Examples 27 and 28 in Table 2 show that NbN x 、TiN x As ZrN XWhen the base layer other than ZrN is used, the orientation in the c-axis direction is estimated from the peak intensity ratio obtained by XRD measurement of the piezoelectric film composed of AlN with a film thickness of 1 μm, and the arithmetic mean roughness (Ra) is measured by AFM. It can be seen that in Examples 27 and 28, the peak intensity ratio of {(101) plane / (002) plane} is greater than 0.25, and sufficient orientation cannot be obtained. It is known that although ZrN x 、NbN x 、TiN x In many cases, materials constituting the base layer are equivalently regarded as transition metal nitrides. However, in the piezoelectric laminate of the present embodiment, a unique effect can be obtained by using zirconium nitride for the base layer.

[0190] The present invention is described in detail with reference to specific embodiments, but it is clear to those skilled in the art that various changes and modifications may be added without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese Patent Application No. 2022-080483) filed on May 16, 2022, and its contents are incorporated herein by reference.

[0191] Explanation of symbols

[0192] 100: Piezoelectric laminate

[0193] 101: Substrate

[0194] 102: Electrode layer

[0195] 103: Basal layer

[0196] 104: Piezoelectric film

[0197] 105: Laminated film

Claims

1. A piezoelectric laminate comprising a substrate and a laminate film provided on at least one surface of the substrate, The laminated film includes an electrode layer, a base layer, and a piezoelectric film in order from the substrate side. The base layer is in contact with the piezoelectric film, The base layer contains zirconium nitride, The piezoelectric film has a hexagonal wurtzite structure oriented in a c-axis direction.

2. The piezoelectric stack according to claim 1, wherein The piezoelectric film contains aluminum nitride, The aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

3. The piezoelectric stack according to claim 1, wherein The zirconium nitride has the chemical formula ZrN X It means that the degree of nitridation represented by x in the chemical formula is in the range of 1<x<2.

4. The piezoelectric stack according to claim 3, wherein: The nitriding degree is in the range of 1.1<x<1.

65.

5. The piezoelectric stack according to claim 1, wherein The thickness of the base layer is 0.2nm-40nm.

6. The piezoelectric stack according to claim 5, wherein: The thickness of the base layer is 0.4 nm to 20 nm.

7. The piezoelectric stack according to claim 1, wherein The piezoelectric film has an arithmetic mean roughness (Ra) of 4.0 nm or less.

8. The piezoelectric stack according to claim 1, wherein A ratio of the peak intensity of the (101) plane to the peak intensity of the (002) plane {(101) plane / (002) plane} in an X-ray diffraction pattern measured by an out-of-plane method of the piezoelectric film is 0.25 or less.

9. The piezoelectric stack according to claim 1, wherein: A ratio of a peak intensity of a (101) plane to a peak intensity of a (002) plane {(101) plane / (002) plane} in an X-ray diffraction pattern measured by an out-of-plane method on the piezoelectric film is 0.1 or less.

10. The piezoelectric stack according to claim 1, wherein The piezoelectric film has a thickness of 100 nm to 10 μm. 11 . A piezoelectric element comprising the piezoelectric laminate according to claim 1 .

12. A method for manufacturing a piezoelectric stack, comprising the steps of: Prepare the substrate, and An electrode layer, a base layer and a piezoelectric film are sequentially formed on at least one surface of the substrate, The base layer contains zirconium nitride, The piezoelectric film has a hexagonal wurtzite structure oriented in the c-axis direction. The piezoelectric thin film is formed so as to be in contact with the base layer.

13. The method for manufacturing a piezoelectric stack according to claim 12, wherein: The piezoelectric film contains aluminum nitride, The aluminum nitride has a hexagonal wurtzite structure oriented in the c-axis direction.

14. The method for producing a piezoelectric stack according to claim 12 or 13, wherein: The film formation is performed by a sputtering method.

Citation Information

Patent Citations

  • Piezo-electric element using super-high oriented aluminum nitride thin film, and its manufacturing method

    JP2004006535A

  • Piezoelectric element and its manufacturing method

    JP2004265899A

  • Piezoelectric film, manufacturing method therefor, piezoelectric film laminate, and manufacturing method therefor

    JP2019145677A